2021
DOI: 10.3390/nano11040861
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Removal of Sulfonated Lignite from Oil Wastewater with Multidimensional MgAl-LDH Nanoparticles

Abstract: In this study, hierarchical MgAl-LDH (layered double hydroxide) nanoparticles with a flower-like morphology were prepared under a hydrothermal condition by employing worm-like micelles formed by cetyltrimethylammonium bromide (CTAB) and salicylic acid (SA) as templates. The morphology and structure of the materials were characterized by Brunauer–Emmett–Teller (BET), SEM, and XRD analyses. The performance for the adsorption of sulfonated lignite (SL) was also investigated in detail. FTIR was used to detect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Due to the long-dependence on crude oil as a major source of energy in the last decades, a huge amount of oil-wastewater was produced from the various oil-processing steps and especially those related to oil drilling systems. The estimated oil-wastewater counts are about 250 million barrels per day, containing different organic hazards, such as sulfonated lignite of abundant functional groups, such as sulfonic acid, phenolic, hydroxyl, carboxyl, and ketone groups [109]. Sulfonated lignite is classified as a very hazardous material to humans and the environment, since it is a catching agent of heavy metals and pesticides/herbicides, and it can increase their concentration in water.…”
Section: Ldhs/ldh-based Materials For Removal Of Oil Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the long-dependence on crude oil as a major source of energy in the last decades, a huge amount of oil-wastewater was produced from the various oil-processing steps and especially those related to oil drilling systems. The estimated oil-wastewater counts are about 250 million barrels per day, containing different organic hazards, such as sulfonated lignite of abundant functional groups, such as sulfonic acid, phenolic, hydroxyl, carboxyl, and ketone groups [109]. Sulfonated lignite is classified as a very hazardous material to humans and the environment, since it is a catching agent of heavy metals and pesticides/herbicides, and it can increase their concentration in water.…”
Section: Ldhs/ldh-based Materials For Removal Of Oil Wastewatermentioning
confidence: 99%
“…A rare work describing the role of hierarchical MgAl-LDH in the adsorptive removal of sulfonated lignite was recently published by Zhou et al [109]. The material was hydrothermally synthesized in the presence of CTAB/salicylic acid as directing agents to produce flower/worm-like morphologies of a high surface area and mesoporous structure.…”
Section: Ldhs/ldh-based Materials For Removal Of Oil Wastewatermentioning
confidence: 99%
“…The general chemical formula of LDHs is denoted as [M 2+ 1−x M 3+ x (OH) 2 ] x+ (A n− ) x/n •mH 2 O, where M 2+ and M 3+ represent the divalent and trivalent cations, respectively, A n− is the anion in the interlayer for charge compensation, and x is equal to the molar ratio of M 3+ /(M 2+ +M 3+ ) [10]. LDHs have recently become popular for treating anionic pollutants because of their strong positive surface charge and exchangeable interlayer anions [11]. Alternatively, some studies have indicated that LDHs have been used as agrochemicals or fertilizers because of their potential to control herbicide and nutrient losses [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Lignite is rich in resources [ 29 ], cheap in price, and has a high content of HA organic matter. On the basis of the above background and our previous studies [ 28 ], in this paper, the HA was extracted from lignite with H 2 O 2 as an oxygenation agent.…”
Section: Introductionmentioning
confidence: 99%